Mimetyczna reinterpretacja katastrofy smoleńskiej – Refleksje metodologiczne .......... 417 - Rokicki, Jarosław (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
REINTERPRETING THE 2010 SMOLENSK AIRPLANE CRASH – A MIMETIC AFTERTHOUGHTThis essay refers to the author’s two papers (2011, 2012) on the socio-cultural outcomes of the plane crash in which Polish President Lech Kaczyński and 95 other high ranking Polish officials lost their lives. Although the dates of the publications suggest otherwise, the 2012 thesis was written earlier than the 2011 paper. The 2012 paper analyses the way the Polish society has dealt with the trauma Poles experienced after the calamitous, unpredictable event. That early societal response has been centered on the traditional narrative of national martyrology created by the Paris Great Emigration of the Poles after the fall of the November Uprising of 1830–1831. The story was built around three literary topoi of Poland tormented, Poland betrayed, and Poland as the Christ of Nations. In the 2011 paper the author decided to use René Girard’s concept of the scapegoat mechanism for the further analysis. The present essay has three goals. It explains the reasoning behind Rokicki’s choice of the scapegoat mechanism to conceptualize the frame of collective perception the Polish society created for an acceptable justification of the crash. The second goal lies in the necessity to explain what happened after the first phase of the scapegoat cycle. It had not run out but created a kind of a national-religious social movement which – animated, ritualized, and institutionalized by Jarosław Kaczyński and his Law and Justice Party – dominated the political scene in Poland for the period until the 2023 October parliamentary election. The third goal is to present the possibilities the mimetic methodology offers for the study of migratory processes, ethnicity, assimilation, and multiculturalism.